The Relationship of Social Support with Optimism in Cancer Survivors in RS. Moh. Hoesin Palembang - Yaneta Nurul Putri; Zaharuddin Zaharuddin; Inda Purwasih (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine the relationship between social support with optimism in cancer survivor at Dr. Moh Hoesin Hospital Palembang. The type of research used is quantitative. The sample in this study amounted to 52 Cancer survivors aged 20-60 years. Measurement of validity in this study using the SPSS Statistic version 25 program, which uses the Pearson product moment correlation analysis method. The research instrument used is the Social Support scale with the Optimism scale. The research instrument used is a social support scale based on the social support aspect of Nervousino, namely emotional or esteem support, tangible or instrumental support, informational support, and companionship support with an optimism scale based on aspects of Seligman's theory consisting of personalization, permanence, and pervasiveness. The results of the Hypothesis test showed a significant value of 0.393 where p <0.004, the results of the hypothesis testing that social support had a relationship with optimism at Dr. Moh Hoesin Hospital Palembang. So it can be stated that the proposed hypothesis is proven.